A CRITICAL EDITION OF "SARMATIAE EUROPEAE DESCRIPTIO" AND "KRONIKA SARMACYJEJ EUROPSKIEJ" (CHRONICLES OF EUROPEAN SARMATIA) BY ALEKSANDER GWAGNIN – THE GOALS, PREMISES, AND INITIAL IMPLEMENTATION OF THE PROJECT - Kuran, Michał (Prace Polonistyczne, 2025)
By presenting the premises and the initial phase of the research project “Critical edition of Sarmatiae Europeae descriptio and Kronika Sarmacyjej Europskiej (Chronicles of European Sarmatia) by Aleksander Gwagnin”, funded by the National Programme for the Development of the Humanities as part of the module “Cultural heritage of the eastern lands of the former Polish-Lithuanian Commonwealth”, the article proposes a framework for reconciling diverse disciplinary methodologies within the field of editing. It discusses the issue of standardization and the formal aspects of developing a digital edition. It also briefly outlines the foundations of editions of Gwagnin’s chronicle in Latin and Polish and explores the purpose of their compiling by Gwagnin, compilation as a creative method, subsequent reprints, and the reasons for their production in the eighteenth century. Kuran examines the text’s availability in digital libraries, title variants of the old print, and modifications to its composition over time. He justifies the transliteration of the text (valued for its timeless) and its transcription (regarded as an interpretation) by addressing different needs of academic disciplines (literary studies, linguistics, history, etc.). This discussion is set within the context of current editorial practices, especially analogue methods, such as phototype, and modern digital approaches to presenting works online. The article outlines the criteria for selecting the base text for the (hybrid) edition, alongside related problems. Emphasis is placed on editing Gwagnin’s entire work, rather than its specific copy. Kuran also highlights the importance of the illustrations in the new edition for capturing the atmosphere of the text. He addresses the specificity and chronology of the publishing framework and changes in the composition of books VII and VIII, as well as discussing the re-composition of the first book, including the accompanying changes in illustrations. All of the steps taken by the former publisher reveal publishing variants within the edition previously considered to be uniform. A key focus of this analysis is the exploration of a new approach to editing which uses technology and grants digital access to the edition while integrating current antilog practices. The new edition is intended to facilitate full-text searches of the work, encompassing both its transliterations and transcriptions.